Adsorption of Cations from a Cement Suspension onto Lignocellulosic Substrates and its Influence on Cement Setting - Pereira, C; Caldeira Jorge, F; Ferreira, J M F (Journal of Wood Chemistry and Technology, 2005)
Abstract The calcium (Ca), sodium (Na), and potassium (K) contents of blue gum, maritime pine, and cork increased after these lignocellulosics were stirred with the filtrate of a cement suspension or a solution of calcium hydroxide. The adsorbed cations could be released easily by treatment with an acidic solution. It is suggested that those raw materials, and lignocellulosics in general, act as cation exchange substrates when they are mixed with cement and water to make wood?cement composites. The implications that such phenomena may have on cement hardening reactions, and how they could hinder them are discussed. The possibility that the phenomenon is related to well?known compatibility problems that many woods present when manufacturing wood?cement composites is discussed.
doi: 10.1080/02773810500366672
Keywords: Adsorption; cations; cement; hindrance; interactions; lignocellulosics

Adsorption of Cations from a Cement Suspension onto Lignocellulosic Substrates and its Influence on Cement Setting - Pereira, C.; Caldeira Jorge, F.; Ferreira, J. M. F. (Journal of Wood Chemistry and Technology, 2005)
Abstract The calcium (Ca), sodium (Na), and potassium (K) contents of blue gum, maritime pine, and cork increased after these lignocellulosics were stirred with the filtrate of a cement suspension or a solution of calcium hydroxide. The adsorbed cations could be released easily by treatment with an acidic solution. It is suggested that those raw materials, and lignocellulosics in general, act as cation exchange substrates when they are mixed with cement and water to make wood?cement composites. The implications that such phenomena may have on cement hardening reactions, and how they could hinder them are discussed. The possibility that the phenomenon is related to well?known compatibility problems that many woods present when manufacturing wood?cement composites is discussed.
doi: 10.1080/02773810500366672doi: 10.1080/02773810500366672The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Adsorption; cations; cement; hindrance; interactions; lignocellulosics

Apoplastic Solute Concentrations of Organic Acids and Mineral Nutrients in the Leaves of Several Fagaceae - Gabriel, Reinhard; Kesselmeier, Jürgen (Plant and Cell Physiology, 1999)
Ion chromatographic methods determined organic acids and main nutrient minerals in the apoplastic solution from leaves of several Fagaceae (Quercus ilex L., Quercus cerris L., Quercus virgiliana (Ten.) Ten, and Fagus sylvatica L.). The anions of organic acids found in high amounts (250 to 650 μM) were quinate, malate, and oxalate. Lactate, pyruvate, formate and acetate were detected in relatively low amounts with concentrations between 20 and 200 μM. The total concentration of organic acids in the apoplastic sap ranged between 1.5 and 2 mM. The total concentration of inorganic cations (K+, Mg2+, NH4+, Ca2+, Na+) and anions (C1−, NO3−, SO2−4 and PO3−4) in the apoplastic sap varied between 5 and 10 mM, and 0.35 and 1.8 mM, respectively. We conclude that the concentration of organic acid ions in the leaf apoplast depends mainly on the exchange with the leaf cells and is influenced by the electrochemical gradient between the symplast and the apoplast in relation to the water potential of the leaf. The determination of formate and acetate in the apoplastic compartment of leaves lend weight to the argument that the production of these acids by trees is a important emission source to the atmosphere.
Keywords: Anions; Apoplast; cations; Fagaceae; leaf; organic acids

Apoplastic Solute Concentrations of Organic Acids and Mineral Nutrients in the Leaves of Several Fagaceae - Gabriel, Reinhard; Kesselmeier, Jürgen (Plant and Cell Physiology, 1999)
Ion chromatographic methods determined organic acids and main nutrient minerals in the apoplastic solution from leaves of several Fagaceae (Quercus ilex L., Quercus cerris L., Quercus virgiliana (Ten.) Ten, and Fagus sylvatica L.). The anions of organic acids found in high amounts (250 to 650 μM) were quinate, malate, and oxalate. Lactate, pyruvate, formate and acetate were detected in relatively low amounts with concentrations between 20 and 200 μM. The total concentration of organic acids in the apoplastic sap ranged between 1.5 and 2 mM. The total concentration of inorganic cations (K+, Mg2+, NH4+, Ca2+, Na+) and anions (C1−, NO3−, SO2−4 and PO3−4) in the apoplastic sap varied between 5 and 10 mM, and 0.35 and 1.8 mM, respectively. We conclude that the concentration of organic acid ions in the leaf apoplast depends mainly on the exchange with the leaf cells and is influenced by the electrochemical gradient between the symplast and the apoplast in relation to the water potential of the leaf. The determination of formate and acetate in the apoplastic compartment of leaves lend weight to the argument that the production of these acids by trees is a important emission source to the atmosphere.
Keywords: Anions; Apoplast; cations; Fagaceae; leaf; organic acids